Antidepressant Activity of Agarwood Essential Oil: A Mechanistic Study on Inflammatory and Neuroprotective Signaling Pathways - Shunan Zhang; Xiqin Chen; Canhong Wang; Yuanyuan Sun; Bao Gong; Dan Li; Yulan Wu; Yangyang Liu; Jianhe Wei (Pharmaceuticals)
Background: Depression ranks among the most severe mental health conditions, and poses a burden on global health. Agarwood, an aromatic medicinal plant, has shown potential for improving mental symptoms. As a common folk medicine, agarwood has been applied as an alternative method for mental disorders such as depression through aromatherapy. Previous studies have found that the therapeutic effects of agarwood aromatherapy are primarily related to its volatile components. This study aimed to examine the antidepressant properties and underlying mechanisms of agarwood essential oil (AEO), a collection of the volatile components of agarwood utilized through aromatherapy inhalation and injection administration in mice. Methods: A lipopolysaccharide (LPS)-induced inflammatory depression model was used to evaluate the effects of AEO inhalation and injection on depression-like symptoms. Behavioral assessments included the open-field, tail suspension, and forced swimming tests. Western blot (WB) and ELISA techniques were used to further verify the mechanistic insights. Results: In the LPS-induced depression-like model, AEO inhalation and injection significantly improved depression-like symptoms, decreased immobility duration in both the tail suspension and forced swimming tests in model mice, and reduced the levels of inflammatory cytokines IL-1β, IL-6, and TNF-α. WB experiments demonstrated that AEO inhibited the NF-κB/IκB-α inflammatory pathway and activated the BDNF/TrkB/CREB pathway in the hippocampus of the LPS-depression model mice. Notably, AEO extracted by hydrodistillation was more effective in alleviating LPS-induced depressive-like behaviors than using supercritical CO2 fluid extraction. Conclusions: Both the inhalation and the injection administration of AEO exerted notable antidepressant effects, potentially associated with reducing inflammation levels in the brain, downregulating inflammatory NF-κB/IκB-α, and upregulating the neuroprotective BDNF/TrkB/CREB signaling pathway. In the future, it is necessary to further determine the pharmacodynamic components, key targets and specific molecular mechanisms of AEO’s antidepressant effects so as to provide more support for the neuroprotective research of medicinal plants.